TINJAUAN HUKUM EKONOMI SYARIAH TERHADAP PERATURAN PRESIDEN NOMOR 76 TAHUN 2020 TENTANG PENGEMBANGAN KOMPETENSI KERJA MELALUI PROGRAM KARTU PRAKERJA - Wulandari, Hindun; Antasari, Rr Rina; Afriansyah, Syafran (Muamalah, 2021)
ABSTRACT Unemployment is a serious problem that until now the Indonesian government has not been able to solve it. Like a younger sibling, unemployment and poverty areinseparable. Because with the increase in unemployment, the poverty level in this countrywill automatically increase. The government as the holder of policy authority is expectedto be able to play a role in overcoming unemployment and poverty problems. From these problems the authors are interested in taking the title of a thesis reviewof sharia economic law against presidential regulation number 76 of 2020 amendments topresidential regulation number 36 of 2020 concerning the development of work potentialthrough the pre-employment card program, which is to find out what is the legal basis froma philosophical point of view. , sociological, and juridical creation of pre-employmentcards, as well as a review of sharia economic law in terms of the principle of benefit andthe principle of justice. The results of this study are the philosophical foundation of this preemploymentcard policy. Realizing justice in the goals of the State, namely realizing the welfare of theIndonesian nation, from a sociological basis, namely to the people's need for decent workto achieve community welfare and from a juridical perspective, namely providing a clearlegal basis. against the corruption eradication commission that corruption destroys everyorder of life of a nation. and from the principle of benefit, namely helping to reducetraining costs borne by participants as well as getting training modules and in terms of theprinciple of justice, justice in terms of the pre-employment card program is only justice inincentive costs and facilities pre-employment card. Key words: Unemployment, Policy, Covid-19